2014
DOI: 10.1007/s12035-014-9015-z
|View full text |Cite
|
Sign up to set email alerts
|

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations

Abstract: In recent years, genome-wide association studies (GWASs) have identified many novel susceptible genes/loci for Alzheimer's disease (AD). However, most of these studies were conducted in European and populations of European origin, and limited studies have been performed in Han Chinese. In this study, we genotyped 14 single-nucleotide polymorphisms (SNPs) in eight GWAS-reported AD risk genes in 1509 individuals comprising two independent Han Chinese case-control cohorts. Four SNPs (rs11234495, rs592297, rs67673… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…In stage 2, we recruited 345 patients (AD2), 337 healthy individuals from the general populations (PC2) and 504 healthy longevity individuals (LC, age 93 ± 2.6 years; as another control) from Southwest China. Most of these AD patients had been analyzed for other risk loci in our recent studies (Bi et al, 2015;Bi et al, 2014;Wang et al, 2014). In brief, patients were diagnosed following the DSM-IV and the NINCDS-ADRDA criteria independently by at least two senior clinicians.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stage 2, we recruited 345 patients (AD2), 337 healthy individuals from the general populations (PC2) and 504 healthy longevity individuals (LC, age 93 ± 2.6 years; as another control) from Southwest China. Most of these AD patients had been analyzed for other risk loci in our recent studies (Bi et al, 2015;Bi et al, 2014;Wang et al, 2014). In brief, patients were diagnosed following the DSM-IV and the NINCDS-ADRDA criteria independently by at least two senior clinicians.…”
Section: Subjectsmentioning
confidence: 99%
“…The selection criteria and details for selected SNPs were described in the supplementary Methods and Table S1. APOE ε4 was determined as previously described (Bi et al, 2015;Bi et al, 2014;Wang et al, 2014).…”
Section: Snp Genotyping and Association Analysismentioning
confidence: 99%
“…The association has been further supported in other populations. For instance, variants of immune-related genes, including complement factor H [10], MS4A [11], CR1 [12], and CD33 [13] are associated with AD susceptibility in Han Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of AD are sporadic AD, which include different susceptible genes/loci and the courses of the disease can be different for each individual (Wang et al, 2016), indicating that epigenetic and environmental factors play an important role in AD etiology. Many studies have shown that methylation plays an essential role in AD occurrence (Zawia et al, 2009).…”
Section: Dna Damage In Admentioning
confidence: 99%